FRI0068 102-wk clinical and radiologic results from the attract trial: a 2 year, randomised, controlled, phase 3 trial of infliximab (remicade®) in pts with active ra despite mtx. (1st June 2001) - Maini, R; Van der Heijde, D; Smolen, J; Kalden, J; Breedveld, F; Emery, P; Keystone, E; Harriman, G; Lipksy, P
Abstract : Background: The ATTRACT trial studied the long term efficacy and tolerability of infliximab in 428 pts with active RA despite MTX (median dose of 15 mg/wk). Objectives: Methods: While continuing MTX, pts were randomly assigned to one of five therapeutic arms in which infliximab at 3 or 10 mg/kg or placebo infusions were given at 0, 2, and 6 wks and every 4 or 8 wks thereafter. Clinical benefit was assessed by maintenance of at least an ACR20 level of response. Using the van der Heijde modified Sharp system assessing bone erosions and joint space narrowing, the total radiologic score (TRS) was calculated for each patient at 0, 30, 54, and 102 wks. Adverse events were tabulated. Results: Infliximab in combination with MTX is well tolerated and results in a sustained clinical benefit at all doses and frequencies over 2 years. Additionally, radiologic progression was essentially arrested in all infliximab plus MTX treatment arms as compared to the MTX control group. All infliximab dose regimens were comparable in clinical and radiologic benefit. No unexpected adverse events, nor an increase in any previously observed side effect were reported. Conclusion: Infliximab in combination with MTX is well tolerated and results in a sustained clinical benefit at all doses and frequencies over 2 years. Additionally, radiologic progression was essentially arrested in all infliximab plus MTX treatment arms as compared to the MTX control group. All infliximab dose regimens were comparable in clinical and radiologic benefit.